CORPORATE FACEBOOK PRACTICE AND ITS EFFECT TO THE ACCOUNTABILITY OF CSR STRATEGY - Satrian, Arif; Adrianto, Zaldy (Jurnal Ekonomi dan Bisnis, 2018)
Social media, such as Facebook, creates an important opportunity for corporation to increase stakeholder’s engagement. On the other hand, the benefits of CSR strategy are depending on stakeholder awareness and engagement. This study examines the corporate Facebook practice that affect the accountability of CSR strategy, with the level of stakeholder engagement as an intervening variable. Based on content analysis of corporate official Facebook pages and CSR report from company website, research data are collected from 30 companies listed on Kompas 100 index. The data analyzed by using descriptive analytic research method and simple regression. The results shows that corporate Facebook practice have a positive significant effect on the level of stakeholder engagement. Moreover, the level of stakeholder engagement has a positive significant effect on CSR strategy accountability. The analyses also show corporate Facebook practice and CSR strategy accountability also positive significantly mediated by stakeholder engagement as intervening variable